2010
DOI: 10.1007/s00127-010-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of mental health and well-being within rural and remote communities

Abstract: The chief determinants of current well being were those reflecting individual level attributes and perceptions, rather than district-level rural characteristics. This has implications for strategies to promote well being within rural communities through enhancing community connectedness and combating social isolation in the face of major adversities such as drought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(129 citation statements)
references
References 43 publications
10
116
1
2
Order By: Relevance
“…Risky lifestyle behaviours such as smoking and drinking and individual psychiatric problems over time could be indicators of perception on neighbourhood dissatisfaction, although the mechanisms going through the same or different pathways are yet to be confirmed by future longitudinal studies. Consistent with previous community studies, (Kelly et al, 2011) district level of urbanisation characteristics were not significantly related. In spite of strong associations observed in adolescents with abnormal psychiatric symptoms, those who were classified as borderline also more reported dissatisfaction toward their neighbourhoods.…”
Section: Previous Research and Synthesis Of Current Knowledgesupporting
confidence: 92%
“…Risky lifestyle behaviours such as smoking and drinking and individual psychiatric problems over time could be indicators of perception on neighbourhood dissatisfaction, although the mechanisms going through the same or different pathways are yet to be confirmed by future longitudinal studies. Consistent with previous community studies, (Kelly et al, 2011) district level of urbanisation characteristics were not significantly related. In spite of strong associations observed in adolescents with abnormal psychiatric symptoms, those who were classified as borderline also more reported dissatisfaction toward their neighbourhoods.…”
Section: Previous Research and Synthesis Of Current Knowledgesupporting
confidence: 92%
“…For example, a recent study found no relationship between drought and mental health indicators (24), possibly implying an association between drought and suicide but not between drought and depression. Such an approach may help disentangle the numerous putative risk factors for rural and farmer suicide in NSW, revealing a clearer picture of the influence of drought on suicide.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously examined cross-sectional determinants of mental health and wellbeing across a rural sample in Australia and demonstrated a significant independent effect of aspects of social networks and support (such as sense of community) on levels of psychological symptoms [21]. The current report examines the role of such variables in relation to SI in order to undertake a more fine grained analysis of the factors underlying rural suicide.…”
Section: Introductionmentioning
confidence: 99%